2015
DOI: 10.1093/trstmh/trv048
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the disparity in estimates of microfilaraemia and antigenaemia in lymphatic filariasis surveys: Figure 1.

Abstract: BackgroundThe diagnosis of lymphatic filariasis (LF) is based typically on either microfilaraemia as assessed by microscopy or filarial antigenaemia using an immuno-chromatographic test. While it is known that estimates of antigenaemia are generally higher than estimates of microfilaraemia, the extent of the difference is not known.MethodsThis paper presents the results of an extensive literature search for surveys that estimated both microfilaraemia and antigenaemia in order to better understand the disparity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…Estimation of prevalence through the use of an immuno-chromatographic card test (ICT) has rapidly become the more popular method of estimating prevalence compared to measuring mf in the peripheral blood due to its cheaper cost, easier implementation and relatively little training to perform [ 35 ]. Open questions remain in how to relate the ICT prevalence to the mf prevalence however, due to ICT measuring an antigen secreted from adult worms as opposed to measuring adult worms directly [ 36 ]. Here, we improve on previous modelling work by using the presence of adult worms in an individual as an indicator of a positive ICT and hence measuring the antigen prevalence for given scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of prevalence through the use of an immuno-chromatographic card test (ICT) has rapidly become the more popular method of estimating prevalence compared to measuring mf in the peripheral blood due to its cheaper cost, easier implementation and relatively little training to perform [ 35 ]. Open questions remain in how to relate the ICT prevalence to the mf prevalence however, due to ICT measuring an antigen secreted from adult worms as opposed to measuring adult worms directly [ 36 ]. Here, we improve on previous modelling work by using the presence of adult worms in an individual as an indicator of a positive ICT and hence measuring the antigen prevalence for given scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of mf and prevalence of antigenaemia were modelled separately due to a poor correlation between outcomes and the inability to predict one from another, as detailed elsewhere [ 43 ]. Bayesian geostatistical models, which included both fixed and random effects, were used to predict the spatial distribution of each outcome.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline relationship across different settings shows high variance with the prevalence of mf below the prevalence of ICT. 10 Post-MDA, the prevalence of mf is lowered while the prevalence of ICT remains high. After several rounds of MDA this leads to a flattened distribution, where the mf positives are fewer than the ICT positives.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is currently a lack of good correspondence between the antigen and microfilaraemia prevalence. 10 A recent study compared the ICT and mf prevalence in both pre- and post-intervention settings and found that no covariates could explain the discrepancy between the two and suggested that predicting mf prevalence from ICT prevalence remains an open problem. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation